Entry Strategies for Video Game Platforms to Expand to China - Shen, Handa (2017)
Over last 40 years, the video games have experienced a quick speed in their development and they have already become one of the most popular life styles of the modern entertainment. Therefore, video game platforms as distributors of video games have enjoyed a great risk these years. China with the world largest population which dedicate to a huge market where there are unlimited profits for those video game platform companies to enter into. This dissertation is mainly aiming to using entry strategy planning theory to explain and explore the entry strategies for game platform companies to enter into Chinese market. Firstly, it explored the reasons for game platform companies to enter into China and the Chinese environment for international video game platforms. Secondly, it has discussed the strategies international video game platform companies have planned according to the literature reviewed and analysis. Thirdly, it generated the recommendations for the new international video game platform companies who want to enter into China.